FORMING OF INCLUSIVE TOURISM OF TERRITORIAL COMMUNITIES AS THE BASIS OF SOCIALLY RESPONSIBLE TERRITORY MARKETING - Безугла, Людмила; Куваєва, Тетяна; Андрусів, Уляна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
It is established that the formation of inclusive tourism is caused by the desire to attract and integrate people with special needs into active social life. This situation is due to the growing use of tourism as a tool for social integration, including to achieve sustainable development goals. It is revealed that inclusive tourism is a key element in the formation of tourist, social and economic potential of individual territorial communities and the country as a whole. The main effect of achieving significant social change through inclusive tourism has been studied. It is proved that the formation of inclusive tourism can ensure the competitiveness of local communities and improve the marketing of territories. In the conditions of economic globalization, territorial communities are at the center of the tasks of development the strategies for positioning regions and increasing their attractiveness. Territory is both a factor in building capacity and an object of study. It is determined that inclusive tourism provides attractiveness of the territory and provides growth of its investment attractiveness. It has been proven that local communities need to implement real strategies to differentiate themselves and continue to attract new visitors. The implementation of marketing involves a series of actions in the short and medium term in order to convince tourism entities of the feasibility of investing or reinvesting in it. It has been identified that the ability to attract and retain visitors and businesses is a key issue in inclusive tourism development strategies. At the same time, inclusive tourism is an important component of sustainable development. It is proved that in Ukraine not enough attention is paid to the formation of inclusive tourism within the development of the concept of sustainable development, namely ensuring safe and comfortable tourism for all visitors, regardless of gender, race, physical disabilities and more. Despite the great opportunities for the development of inclusive tourism, there are a number of problems, including: underdeveloped infrastructure, poor quality of services, lack of barrier-free environment for people with disabilities.